EXPLAINING CAPITAL STRUCTURE IN AGRIBUSINESS: evidence from farms, agricultural organizations, and research frontiers - Carolina Garcia, Deny; Gimenes, Régio Marcio Toesca; Peruzzi , Adriana Zeponi; Junior, Nelson Tsuji; Cavalheiro, Rafael Todescato (Encontro Internacional de Gestão, Desenvolvimento e Inovação (EIGEDIN), 2026)
This article examined how the literature has explained capital structure in agribusiness, with an emphasis on the theories employed and the determinants of financing decisions in agricultural holdings and related organizations. To this end, a systematic literature review was conducted based on Scopus and Web of Science, analyzing a sample of 47 articles published from 2013 onward, whose interpretive core focused on studies centered on farms and farmers. The results indicated that the literature is theoretically plural, yet unevenly consolidated. Pecking Order Theory and Trade-Off Theory were the most recurrent approaches, while risk-based and optimal debt models gained relevance under conditions of uncertainty. The determinants of capital structure were organized into four interconnected dimensions: economic and financial variables, farm characteristics, financing conditions and the institutional environment, and human, organizational, and management factors. Financing decisions resulted from the interaction among these elements. The article contributed by integrating theoretical approaches, systematizing key determinants, and identifying gaps for future research.